2019
DOI: 10.1159/000495907
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac MRI-Proven Myocarditis Mimicking ST-Elevation Myocardial Infarction after a Cobra Bite

Abstract: Cardiac complications following snake envenomation occur infrequently. Myocarditis, as a consequence of the toxic effect of the snake venom, is rare, and only a few cases have been reported. We present a case of an 84-year-old man who was envenomed by a cobra. In addition to respiratory failure due to neurotoxicity of the venom, cardiac abnormalities including elevated cardiac markers and abnormal electrocardiogram were found. The findings on cardiac magnetic resonance imaging confirmed the diagnosis of acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…Research is lacking; however, many case studies have postulated that snake venom may have thrombotic and vasoconstricting properties along with inflammatory components. 3,4 Bashir and Jenkins postulate that snake venom from vipers contains endopeptidases that can deplete coagulation factors leading to a hypercoagulable state. 3 This consumption of coagulation factors can lead to small or large occlusions explaining myocardial infarction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Research is lacking; however, many case studies have postulated that snake venom may have thrombotic and vasoconstricting properties along with inflammatory components. 3,4 Bashir and Jenkins postulate that snake venom from vipers contains endopeptidases that can deplete coagulation factors leading to a hypercoagulable state. 3 This consumption of coagulation factors can lead to small or large occlusions explaining myocardial infarction.…”
mentioning
confidence: 99%
“…3 Another study reported a case of MRI-confirmed myocarditis mimicking an STEMI. 4 Hypersensitivity and inflammatory reaction to cardiac myocytes were postulated to be the causes of this myocarditis.…”
mentioning
confidence: 99%